Implementasi Metode Extreme Programming Pada Aplikasi Pengelolaan Sewa Mobil Berbasis Web - Moh. Fauzan; Noor Al Azzam, Mohammad (Universitas PGRI Kanjuruhan Malang, 2023)
To design and develop a web-based car rental management application for the case study of Zalfa Rent Car writer uses the Extreme Programming (XP) method. The main objective of this research is to increase the efficiency and effectiveness of the car rental management process within the company. The first step in this research is to analyze the needs at Zalfa Rent Car related to car rental management. Next, application development begins using the XP cycle. After development is complete, final testing is carried out to verify that the application has met the needs and requirements that have been needed. The test results will be evaluated to identify deficiencies and make the necessary improvements. It is hoped that the results of this research will produce a web-based car rental management application that is efficient, reliable, and in accordance with the needs of Zalfa Rent Car. This research also contributes to an understanding of the application of the Extreme Programming method in developing web-based software for the car rental industry. Keywords: Car Rental Management Application, Web Based, Extreme Programming